Job Satisfaction and Organizational Commitment as Determinants of Turnover Intention: Evidence from Antero Hamra Regional Unit Hospital in Kendari - Imran Hatta; Sartini Risky; Wa Ode Nova Noviyanti Rachman (Magister Kesehatan Universitas Mandala Waluya, 2026)
Introduction: The employee turnover rate at Regional Unit Hospital Antero Hamra, Kendari City, has increased in the last three years, where in 2022 it was 10.41%, in 2023 it was 14.28%, and in 2024 it was 17.97% and is in the high category, many employees intend to do turnover or leave the hospital because their current posit ion does not match their wishes. Because of this, researchers are interested in analyzing job satisfaction and organizational commitment as determinants of turnover intention: evidence from Antero Hamra Regional Unit Hospital in Kendari. Method: Quantitative research with an analytical survey approach with a cross-sectional research design. Sample selection was carried out using the proportionate stratified random sampling method. The research sample consisted of 98 employees. The measuring instrument used was a questionnaire. Data analysis used was multiple linear regression analysis. Result: The effect of job satisfaction (0.000) and organizational commitment (0.000) on employee turnover intention at Antero Hamra Hospital, Kendari City with a significance value of less than 0.05. Turnover intention in the low category was 63 respondents (64.3%), job satisfaction in the high category was 74 respondents (64.3%), organizational commitment in the high category was 80 respondents (81.6%). Conclusion: There is an influence of the variables of job satisfaction, organizational commitment, work environment, and compensation on the intention to quit employees at Antero Hamra Regional Hospital, Kendari City.